THE CHALLENGES OF ISLAMIC EDUCATION IN A GLOBAL CONTEXT - Yudi Ardian Rahman (Tsaqofah : Jurnal Pendidikan Islam, 2024)
Globalization is a complex phenomenon that has had far-reaching effects. Not surprisingly, the term, "globalization" has acquired multiple connotations of meaning. On the one hand, globalization is seen as an irresistible and benign force for delivering economic prosperity to people around the world. On the other hand, it is blamed as the source of all contemporary ills. The era of globalization, marked by quality competition, requires all parties in various fields and sectors of development to constantly increase competition. The era of free markets, or what is commonly referred to as the era of globalization, has often been echoed by economic observers since several decades ago until now. In the era of globalization, knowledge and technology, which are the source of materials to be studied, are developing so fast that in such conditions the demands on the quality of human resources are highly prioritized, and if we note that in this era of globalization what is needed is how we can be accepted in any part of the world. Keywords: Educational Challenges, Islam, in a Global Context